Arithmetic-Geometric Series App 2.

Calculus Level 4

Let x < 1 |x| < 1 and f ( x ) = n = 0 ( a + n d ) x n f(x) = \sum_{n = 0}^{\infty} (a + nd)x^n and g ( x ) = n = 0 ( a + n 2 d ) x n g(x) = \sum_{n = 0}^{\infty} (a^{*} + n^2 d^{*})x^n and f ( 1 2 ) = g ( 1 2 ) = 2 f(\dfrac{1}{2}) = g(\dfrac{1}{2}) = 2 and f ( 1 2 ) = g ( 1 2 ) = 2 9 f(-\dfrac{1}{2}) = g(-\dfrac{1}{2}) = \dfrac{2}{9} .

The volume V V formed when the region bounded by f ( x ) f(x) and g ( x ) g(x) on [ 1 2 , 1 2 ] [-\dfrac{1}{2},\dfrac{1}{2}] is revolved about the x x axis can be expressed as V = α β π V = \dfrac{\alpha}{\beta}\pi , where α \alpha and β \beta are coprime positive integers.

Find α + β \alpha + \beta .

Refer To Previous Problem


The answer is 23813.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Aug 3, 2018

Let x < 1 |x| < 1 .

f ( x ) = n = 0 ( a + n d ) x n = a n = 0 x n + d n = 1 n x n = f(x) = \sum_{n = 0}^{\infty} (a + nd)x^n = a\sum_{n = 0}^{\infty} x^n + d\sum_{n = 1}^{\infty} nx^n = a 1 x + d j = 1 n = j x n = \dfrac{a}{1 - x} + d\sum_{j = 1}^{\infty}\sum_{n = j}^{\infty} x^n = a 1 x + d 1 x j = 1 x j = a 1 x + d 1 x ( x 1 x ) = a 1 x + d x ( 1 x ) 2 \dfrac{a}{1 - x} + \dfrac{d}{1 - x}\sum_{j = 1}^{\infty} x^{j} = \dfrac{a}{1 - x} + \dfrac{d}{1 - x}(\dfrac{x}{1 - x}) = \boxed{\dfrac{a}{1 - x} + \dfrac{dx}{(1 - x)^2}}

and,

g ( x ) = n = 0 ( a + n 2 d ) x n = a n = 0 x n + d n = 1 n 2 x n = a 1 x + d j = 1 n = j n x n = g(x) =\sum_{n = 0}^{\infty} (a^{*} + n^2 d^{*})x^n = a^{*}\sum_{n = 0}^{\infty} x^n + d^{*}\sum_{n = 1}^{\infty} n^2 x^n = \dfrac{a^{*}}{1 - x} + d^{*}\sum_{j = 1}^{\infty}\sum_{n = j}^{\infty} n x^n = ( a 1 x + d j = 1 ( j x j + ( j + 1 ) x j + 1 + ( j + 2 ) x j + 2 + . . . ) = (\dfrac{a^{*}}{1 - x} + d^{*}\sum_{j = 1}^{\infty} (j x^{j} + (j + 1)x^{j + 1} + (j + 2)x^{j + 2} + ... ) = a 1 x + d ( 1 1 x j = 1 j x j + x ( 1 x ) 2 j = 1 x j ) = \dfrac{a^{*}}{1 - x} + d^{*}(\dfrac{1}{1 - x}\sum_{j = 1}^{\infty} j x^{j} + \dfrac{x}{(1 - x)^2}\sum_{j = 1}^{\infty} x^{j}) = a 1 x + d ( ( 1 1 x ) ( x ( 1 x ) 2 ) + ( x ( 1 x ) 2 ) ( x 1 x ) ) = a 1 x + d ( x 2 + x ( 1 x ) 3 ) \dfrac{a^{*}}{1 - x} + d^{*}((\dfrac{1}{1 - x})(\dfrac{x}{(1 - x)^2}) + (\dfrac{x}{(1 - x)^2})(\dfrac{x}{1 - x})) = \boxed{\dfrac{a^{*}}{1 - x} + d^{*}(\dfrac{x^2 + x}{(1 - x)^3})}

f ( 1 2 ) = 2 f(\dfrac{1}{2}) = 2 and f ( 1 2 ) = 2 9 f(-\dfrac{1}{2}) = \dfrac{2}{9} \implies

3 a d = 1 3a - d = 1

a + d = 1 a + d = 1

a = 1 2 = d f ( x ) = 1 2 ( 1 ( 1 x ) 2 ) 1 2 1 2 ( f ( x ) ) 2 d x = 1 12 ( 1 ( 1 x ) 3 ) 1 2 1 2 = 52 81 \implies a = \dfrac{1}{2} = d \implies f(x) = \dfrac{1}{2}(\dfrac{1}{(1 - x)^2}) \implies \displaystyle\int_{-\frac{1}{2}}^{\frac{1}{2}} (f(x))^2 dx = \dfrac{1}{12}(\dfrac{1}{(1 - x)^3})|_{-\frac{1}{2}}^{\frac{1}{2}} = \boxed{\dfrac{52}{81}} .

g ( 1 2 ) = 2 g(\dfrac{1}{2}) = 2 and g ( 1 2 ) = 2 9 g(-\dfrac{1}{2}) = \dfrac{2}{9} \implies

9 a d = 3 9a^{*} - d^{*} = 3

a + 3 d = 1 a^{*} + 3d^{*} = 1

a = 5 14 \implies a^{*} = \dfrac{5}{14} and d = 3 14 d^{*} = \dfrac{3}{14} g ( x ) = 1 14 ( 5 1 x + 3 ( x 2 + x ) ( 1 x ) 3 ) \implies g(x) = \dfrac{1}{14}(\dfrac{5}{1 - x} + \dfrac{3(x^2 + x)}{(1 - x)^3})

1 2 1 2 ( g ( x ) ) 2 d x = 1 1 4 2 1 2 1 2 25 ( 1 x ) 2 + 30 x ( x + 1 ) ( 1 x ) 4 + 9 x 2 ( x + 1 ) 2 ( 1 x ) 6 d x \displaystyle\int_{-\frac{1}{2}}^{\frac{1}{2}} (g(x))^2 dx = \dfrac{1}{14^2}\displaystyle\int_{-\frac{1}{2}}^{\frac{1}{2}} \dfrac{25}{(1 - x)^2} + \dfrac{30x(x + 1)}{(1 - x)^4} + \dfrac{9x^2(x + 1)^2}{(1 - x)^6} dx

Let I 1 ( x ) = x ( x + 1 ) ( 1 x ) 4 d x I_{1}(x) = \displaystyle\int \dfrac{x(x + 1)}{(1 - x)^4} dx

Letting u = 1 x d x d u I 1 ( x ) = u 2 3 u 3 + 2 u 4 d u = 1 1 x 3 2 ( 1 x ) 2 + 2 3 ( 1 x ) 3 u = 1 - x \implies dx - -du \implies I_{1}(x) = -\displaystyle\int u^{-2} - 3u^{-3} + 2u^{-4} du = \dfrac{1}{1 - x} - \dfrac{3}{2(1 - x)^2} + \dfrac{2}{3(1 - x)^3}

I 1 ( x ) 1 2 1 2 = 92 81 \implies I_{1}(x)|_{-\frac{1}{2}}^{\frac{1}{2}} = \boxed{\dfrac{92}{81}}

Let I 2 ( x ) = x 2 ( x + 1 ) 2 ( 1 x ) 6 d x I_{2}(x) = \displaystyle\int \dfrac{x^2(x + 1)^2}{(1 - x)^6} dx

Letting u = 1 x d x d u I 2 = u 2 6 u 3 + 13 u 4 12 u 5 + 4 u 6 d u = u = 1 - x \implies dx - -du \implies I_{2} = -\displaystyle\int u^{-2} - 6u^{-3} + 13u^{-4} - 12u^{-5} + 4u^{-6} du = 1 1 x 3 ( 1 x ) 2 + 13 3 ( 1 x ) 3 3 ( 1 x ) 4 + 4 5 ( 1 x ) 5 \dfrac{1}{1 - x} - \dfrac{3}{(1 - x)^2} + \dfrac{13}{3(1 - x)^3} - \dfrac{3}{(1 - x)^4} + \dfrac{4}{5(1 - x)^5}

I 2 ( x ) 1 2 1 2 = 2596 1215 \implies I_{2}(x)|_{-\frac{1}{2}}^{\frac{1}{2}} = \boxed{\dfrac{2596}{1215}}

and,

I 3 = 1 2 1 2 ( 1 x ) 2 d x = 1 1 x 1 2 1 2 = 4 3 I_{3} = \displaystyle\int_{-\frac{1}{2}}^{\frac{1}{2}} (1 - x)^{-2} dx = \dfrac{1}{1 - x}|_{-\frac{1}{2}}^{\frac{1}{2}} = \boxed{\dfrac{4}{3}}

1 2 1 2 ( g ( x ) ) 2 = 1 1 4 2 ( 100 3 + 2760 81 + 23364 1215 ) = 2924 6615 \implies \displaystyle\int_{-\frac{1}{2}}^{\frac{1}{2}} (g(x))^2 = \dfrac{1}{14^2}(\dfrac{100}{3} + \dfrac{2760}{81} + \dfrac{23364}{1215}) = \boxed{\dfrac{2924}{6615}}

V = π 1 2 1 2 ( f ( x ) ) 2 ( g ( x ) ) 2 d x = π ( 52 81 2924 6615 ) = 3968 19845 π = α β π α + β = 23813 \implies V = \pi\displaystyle\int_{-\frac{1}{2}}^{\frac{1}{2}} (f(x))^2 - (g(x))^2 dx = \pi(\dfrac{52}{81} - \dfrac{2924}{6615}) = \dfrac{3968}{19845}\pi = \dfrac{\alpha}{\beta}\pi \implies \alpha + \beta = \boxed{23813} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...